A closer look at homework compliance in behavior therapy for bulimia nervosa: does homework compliance in between-session period prospectively predict session-by-session change in bulimia symptoms?. Issue 1 (2nd January 2023) - Srivastava, Paakhi; Parker, Megan N.; Presseller, Emily K.; Wons, Olivia B.; Clark, Kelsey E.; Juarascio, Adrienne S.
ABSTRACT: Introduction: Homework assignments are considered key components of behavioral treatments for bulimia nervosa (BN), but little is known about whether homework compliance predicts BN symptom improvement. The present study is the first to examine whether session-by-session change in homework compliance predicts session-by-session changes in BN symptoms during behavioral treatment. Method: Patients with BN-spectrum eating disorders ( n = 42) received 20 sessions of behavioral treatment. Each session, their clinicians completed surveys assessing compliance with self-monitoring, behavioral, and written homework assignments and BN symptom frequency during the previous week. Results: Significant between-persons effects of self-monitoring and behavioral homework compliance were identified, such that patients with greater compliance in the past week experienced greater reductions in binge eating and purging the following week. There were significant within-persons effects of self-monitoring compliance on binge eating and behavioral homework compliance on restrictive eating, binge eating, and purging, such that greater than one's usual compliance predicted greater improvements in BN symptoms the following week. No significant effects of written homework compliance were identified. Conclusion: Compliance with self-monitoring and behavioral homework predict improvements in BN symptoms during behavioral treatment. These findings reinforce the importance of self-monitoring and behavioral homework compliance as drivers of change during treatment for BN.